Analisis Praktik Trading Saham Syariah Dalam Perspektif Hukum Ekonomi Syariah Studi Kasus IDX Kalimantan Selatan - Muhammad Pajrianor; Parman Komarudin; Umi Hani (Jurnal Penegakan Hukum Indonesia, 2022)
This study aims to analyze the practice of Islamic stock trading in the perspective of Islamic economic law, the case study of the Indonesia Stock Exchange (IDX) in South Kalimantan. Using a qualitative research method with a field research approach, the author goes directly to the field to conduct observations and interviews related to the Islamic stock trading system at Indonesia Stock Exchange (IDX) South Kalimantan. The object of this research is Sharia Stock Trading Practice. The results of this study are that the mechanism for trading in Indonesian sharia shares uses Sharia Online Trading System (SOTS), namely the omission of the Margin Trading and Short Selling features and the shares traded may only be shares included in the Sharia Securities flat. Even though using the Sharia Online Trading System (SOTS) system, it turns out that several transaction activities that are prohibited by Fatwa of the National Sharia Council of the Indonesian Ulema Council include fake demand/supply, pump and dump, cornering, heading behavior and fear of missing out. In the perspective of sharia economic law, the practice of trading sharia shares in a trading mechanism has been declared to be in accordance with the findings of several prohibited practices, which can make the practice of trading sharia shares inconsistent with the principles of sharia economic law.